Feasibility of Electric Property Tomography of pelvic tumors at 3T. Issue 4 (28th April 2014) - Balidemaj, Edmond; van Lier, Astrid L. H. M. W.; Crezee, Hans; Nederveen, Aart J.; Stalpers, Lukas J. A.; van den Berg, Cornelis A. T.
Abstract : Purpose: Investigation of the validity of the "transceive phase assumption" for Electric Property Tomography of pelvic tumors at 3T. The acquired electric conductivities of pelvic tumors are beneficial for improved specific absorption rate determination in hyperthermia treatment planning. Methods: Electromagnetic simulations and magnetic resonance imaging measurements of a pelvic‐sized phantom and the human pelvis of a volunteer and a cervix cancer patient. Results: The reconstructed conductivity values of the phantom tumor model are in good quantitative agreement (mean deviation: 1–10%) with the probe measurements. Furthermore, the average reconstructed conductivity of a pelvic tumor model was in close agreement with the input conductivity (0.86 S/m vs. 0.90 S/m). The reconstructed tumor conductivity of the presented patient ( cervical carcinoma, Stage: IVA) was 1.16 ± 0.40 S/m. Conclusion: This study demonstrates the feasibility of electric property tomography to measure quantitatively the conductivity of centrally located tumors in a pelvic‐sized phantom and human pelvis with a standard magnetic resonance (MR) system and MR sequences. A good quantitative agreement was found between the reconstructed σ ‐values and probe measurements for a wide range of σ ‐values and for off‐axis located spherical compartment. As most pelvic tumors are located in the central region of the pelvis, these results can be exploited in hyperthermia treatment planning systems.Magn Reson Med 73:1505–1513, 2015. © 2014 Wiley Periodicals, Inc.